Analysis of Reactive Power Compensation Using Static Compensator (STATCOM) Technology in Distribution Networks - Juneidi Injos II S; Beni Satria; Solly Aryza (INFOKUM, 2025)
Electricity distribution networks often face efficiency challenges due to uncompensated reactive power, causing power factor degradation, increased power losses, and voltage instability. This study aims to analyze the use of Static Compensator (STATCOM) as a reactive power compensation solution in 20 kV distribution networks, with a focus on improving power factor, reducing power losses, and voltage staability. These challenges are relevant in Indonesia, where growing electricity demand and limited infrastructure exacerbate energy inefficiencies. The research methodology uses a quantitative approach based on simulation in MATLAB/Simulink. A simple distribution network model with one feeder (load 500 kW, 300 kVAR) is created, integrated with a STATCOM with a capacity of 300 kVAR. Simulations are carried out to compare conditions before and after the use of STATCOM at constant and fluctuating loads, measure power factor, power losses, and voltage profiles. The simulation results show that STATCOM improves the power factor from 0.857 to 1.0, reduces power losses by 26.5% (from 425.39 W to 312.50 W), and suppresses voltage drop from 24.51 V to 12.50 V. STATCOM effectively maintains voltage stability under disturbance conditions with a fast response (5-10 ms). However, the high initial cost indicates the need for economic optimization for practical implementation.